New design of titanium plate for minimally invasive treatment of mandibular fractures - Salman, Nour Jihad (2021)
Many treatment modalities and various fixation techniques for maxillofacial fractures were suggested in the literature. Some authors suggested new treatment patterns using different plating techniques, whereas others presented a new macrogeometry of fixation plates that aimed at improving biomechanical properties and material resistance. The purpose of this study is to evaluate, in vitro, the stability of a new model of titanium fixation miniplate for the fixation of maxillomandibular fractures. Therefore, an in vitro experimental study using polyurethane mandibles was conducted to evaluate the biomechanical properties of the new fixation plate (SS group) compared to a 2.0mm four-hole standard plate fixation following the Champy technique as a control (Ch group). In a universal testing machine, the experiments were performed upon fixation, analyzing and comparing the maximum force in Newtons (N), displacement at maximum force in millimeters (mm) and the time till the maximum force in seconds (s) between the two groups. As a result, group Ch showed superior results in fixation and stabilization of mandibular angle fracture, however, this experiment was performed at a mobile bone of the facial skeleton due to facility of performing the biomechanical tests and the presence of an established methodology, while the intended area of use would be facial fractures in non-mobile bones where direct muscle loading is minimal such as fractures of the frontozygomatic complex, zygomaticomaxillary complex, condylar neck and other maxillofacial fractures.